Emotion-Focused Cognitive Behavioral Therapy in Comorbid Obesity With Binge Eating Disorder: A Pilot Study of Feasibility and Long-Term Outcomes - Torres, Sandra; Sales, Célia M. D.; Guerra, Marina Prista; Simões, Maria P.; Pinto, Mariana; Vieira, Filipa M. (Frontiers in Psychology, 2020)
Obesity coupled with binge eating disorder (BED) is an increasing problem. Incorporation of treatment strategies that address both problems in people with comorbid symptoms is of major interest. This study aimed to investigate the feasibility and preliminary long-term outcomes of a brief emotion-focused cognitive behavioral therapy (EF-CBT) program. Ten women with obesity and BED received a group intervention. Standardized outcome measures to assess general distress, emotional processing, eating behavior, and weight loss were completed at baseline, end-of-treatment, 6- and 18-months follow-ups. Individualized outcome measures were also applied to describe the personal experiences during the intervention. Improvements were identified at either post-test or 6-month follow-up in nearly all standardized outcome measures. The exception was found in restrained eating and weight loss. The mean percentage of weight loss at the 18-month follow-up was 4.10% but this change did not reach statistical significance. Maintained improvements were found in some dimensions of general distress (subjective well-being), emotional processing (alexithymia and signs of unprocessed emotions), and eating behavior (external eating). These changes were in line with the participants’ perception of the clinical utility the program in improving emotional awareness and eating control. Further studies are needed to examine EF-CBT intervention effectiveness with a larger sample.